2019
DOI: 10.3390/acoustics1020024
|View full text |Cite
|
Sign up to set email alerts
|

Archaeoacoustic Examination of Lazarica Church

Abstract: The acoustic analysis provides additional information on building tradition and related indoor practice that includes sound, thus deepening our understanding of architectural heritage. In this paper, the sound field of the Orthodox medieval church Lazarica (Kruševac city, Serbia) is examined. Lazarica is a representative of Morava architectural style, developed in the final period of the Serbian medieval state, when also the chanting art thrived, proving the importance of the aural environment in Serbian churc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The reliability of the method used in the present study may be evaluated through the point of view of the so-called archeo-acoustics. A taxonomy of the procedures used in the previous studies [30][31][32][33][34][35][36][37][38][39][40] is shown in Table 2. Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of the method used in the present study may be evaluated through the point of view of the so-called archeo-acoustics. A taxonomy of the procedures used in the previous studies [30][31][32][33][34][35][36][37][38][39][40] is shown in Table 2. Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Lazarica Church [40] Impulse response measurement Calibrated model using on-site measurement results.…”
Section: Palais Du Trocadero [39]mentioning
confidence: 99%
“…In the study, it was stated "a directional sound source might be a better approximation than an omnidirectional sound source for the purpose of the present research". The same approach was followed by Brezina [129] for the measurement of intelligibility and clarity of speech in Romanesque churches and by Dordevic et al [132] for an Orthodox church.…”
Section: Directional Speakermentioning
confidence: 96%
“…Since UNESCO's adoption of the Convention for the Safeguarding of the Intangible Cultural Heritage [2] in 2003, the acoustics and acoustical experiences of churches have been established as an important area of research. The interaction between ritualistic and cultural expressions in churches and their acoustics have been the topic of several research projects [3][4][5][6][7][8][9][10]. The comprehensive review article on church acoustics by Girón et al [11] discusses the efforts of several research teams who have acoustically characterized a large number of churches across the world and, specifically, Europe.…”
Section: Introductionmentioning
confidence: 99%